1999
DOI: 10.1073/pnas.96.4.1201
|View full text |Cite
|
Sign up to set email alerts
|

Volatile buffers can override the “pH memory” of subtilisin catalysis in organic media

Abstract: The protonation state and activity of enzymes in low-water media are affected by the aqueous pH before drying (''pH memory''). However, both protonation and activity will change if buffer ions can be removed as volatile or organic-extractable weak acids or bases. With NH 4 OOCH buffers, in which both ions can be removed, pH memory disappears completely for subtilisin-catalyzed transesterification in hexane. Only weak pH memory is found with buffers having one volatile component, NH 4 -phosphate and NaOOCH. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…This was interpreted as the dried powder having the same effective pH as the solution, and termed “pH memory”, but it was later shown that, in many cases, the degree of ionization in the solid had more to do with the ionic strength of the solution than the pH [125]. Taking ionic strength into account, Li et al [126], showed that H + activity may in fact change substantially upon drying from aqueous solution.…”
Section: Other Factorsmentioning
confidence: 99%
“…This was interpreted as the dried powder having the same effective pH as the solution, and termed “pH memory”, but it was later shown that, in many cases, the degree of ionization in the solid had more to do with the ionic strength of the solution than the pH [125]. Taking ionic strength into account, Li et al [126], showed that H + activity may in fact change substantially upon drying from aqueous solution.…”
Section: Other Factorsmentioning
confidence: 99%
“…Recent studies of the cyclization of amorphous quinapril hydrochloride, colyophilized with citric acid at different initial solution pH, have shown that initial pH, and the glass transition temperature, T g , have an important role in affecting instability 14. Evidence has been presented to show that, in some cases, the degree of ionization of acidic or basic groups appears to be retained from the initial solution to the final lyophilized solid; the term “pH memory” has been coined to describe this behavior 15–17. In this context, an apparent “pH memory” effect also was observed for the inversion of sucrose in the amorphous solid state, in that the rate of chemical reactivity in the freeze‐dried solid, that had identical chemical composition and T g , correlated very well with the pH of the solution before freeze drying 10.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the suggestion that pH and p K a are similar in solution and in freeze‐dried materials15–20 is based on the observation that the extent of corresponding ionizable groups in solution and solid state were similar. However, this does not necessarily mean that pH and p K a remain the same.…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of Subtilisin Carlsberg decreased significantly as the pH rose up. The reason for the decrease of Subtilisin Carlsberg transfer could be attributed to the decrease of electrostatic interaction between Subtilisin Carlsberg (pI= 9.4) [9] and anionic AOT as the pH rose from 5 to 8. This suggested that the transfer of Subtilisin Carlsberg to the reverse micellar phase was driven mainly by the electrostatic interactions between the positive charges of the protein and the opposite charges of AOT hydrophilic moiety.…”
Section: Extraction Of Subtilisin Carlsberg By Aot/isooctane Reverse mentioning
confidence: 95%
“…Subtilisin Carlsberg shows 72% homogenesity with nattokinase. They show similar molecular weight, conformation and isoelectric point [1,9] . In this paper, Subtilisin Carlsberg is taken as a model protein of nattokinase during the investigation of reverse micelles extraction of nattokinase from fermentation broth.…”
mentioning
confidence: 90%